Perspectives for early-career researchers on plagiarism and scientific integrity - Robert G. Young; T. Fatima Mitterboeck (Canadian Science Publishing, 2020)
Lapses in scientific integrity, such as plagiarism, persist in the scientific realm. To be successful and contributory, early-career researchers (ECRs), including graduate students, need to be able to effectively navigate the literature, peer-review process, and scientific research with integrity. Here we discuss different aspects of scientific integrity related to ECRs. Our discussion centres on the concepts of plagiarism and intellectual property, predatory journals, aspects of peer review, transparency in publishing, and false advanced accreditations. Negative elements within these topics may be especially damaging to ECRs, who may be less familiar with the research landscape. We highlight the need for ECRs to approach scientific investigation cautiously and thoughtfully to promote integrity through critical thinking.